Hubungan Antara Kontrol Diri DenganPerilaku Seks Bebas Pada Remaja - Phatriot Hutama, Jhovan, Usmi Karyani, S.Psi.Msi (2016)
Recently, people, especially parents and teachers, often considered teenagers as those who face problems. One of many teenagers' problems is the problem of sex before marriage behavior. This problem becomes a hot topic to be discussed because in the field, many sex-affair behaviors are found among the individuals who are still in the level of formal education and not bound in a marriage. The problem is that the increase of this problem is not only in the frequency but also in the intensity. Therefore, it cannot be ignored that recently, the negative impact of sex misuse disturbs enough the peace in people's life. The hypothesis proposed was: there is a negative correlation between self-control and free-sex behavior. The subjects of this research are students of 11th grade in SMA Negeri 1 Widodaren Ngawi. The technique of sampling which was used was the technique of stratified sampling because the samples were taken in stratification way which consisted of students of 10th grade, 11th grade, and 12th grade X, XI, XII, in which each grade, one sample was taken. Total of the research subjects are as many as 98 students. The tool to collect data used the scale of self-control and the scale of free-sex behavior. The method of data analysis used the technique of product moment correlation. The results of the calculation obtained the score of correlation coefficient (r) as much as -0.328 with a significance 0.001 (p < 0,01). It meant that there was a very significant negative correlation between the self-control and the free-sex behavior. The higher the self-control, the higher the free-sex behavior, and vice versa. The effective contribution revealed how much the role or contribution of the independent variable (self-control) on the dependent variable (free-sex behavior) was. The effective contribution of self-control on the free-sex behavior was 10.7% (rsquare=107), therefore, there was 89.3% of other factors which influenced the free-sex behavior outside the variable of self-control, such as: the environment of association, the parents' parenting pattern, and the past experiences.